2008
DOI: 10.1088/1742-5468/2008/07/p07008
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized natural roads for predicting traffic flow: a sensitivity study

Abstract: In this paper, we extended road-based topological analysis to both nationwide and urban road networks, and concentrated on a sensitivity study with respect to the formation of self-organized natural roads based on the Gestalt principle of good continuity. Both Annual Average Daily Traffic (AADT) and Global Positioning System (GPS) data were used to correlate with a series of ranking metrics including five centrality-based metrics and two PageRank metrics. It was found that there exists a tipping point from seg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
138
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 19 publications
1
138
1
3
Order By: Relevance
“…Figure 8 shows that the traditional road centrality and traffic flow exhibit a high correlation, thereby indicating that the centrality index can be used to analyze the road traffic flow. This finding is consistent with the conclusion in the literature (Jiang et al, 2008). The mean values of the correlation coefficient between traffic flow and the degree, betweenness, and PageRank centralities in every period are 0.73, 0.72, and 0.76, respectively.…”
Section: Correlation Analysis At Line Granularitysupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 8 shows that the traditional road centrality and traffic flow exhibit a high correlation, thereby indicating that the centrality index can be used to analyze the road traffic flow. This finding is consistent with the conclusion in the literature (Jiang et al, 2008). The mean values of the correlation coefficient between traffic flow and the degree, betweenness, and PageRank centralities in every period are 0.73, 0.72, and 0.76, respectively.…”
Section: Correlation Analysis At Line Granularitysupporting
confidence: 93%
“…In particular, network centrality is an important indicator of road network characteristics and has been broadly used in the analysis of urban traffic flow. Jiang et al (2008) studied the formation of self-organized natural roads from the perspective of complex network, and analyzed the correlation between road network centrality and traffic flow based on the joint principles. Betweenness centrality is utilized to characterize urban traffic flow, and the results demonstrate that the traditional betweenness centrality is unsuitable for analyzing the dynamic process of traffic flow and needs to be further improved (Kazerani and Winter, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In their paper, roads are merged from road segments of the same name. Later, Jang and his colleagues (Jiang et al 2008) found the self-organized nature of urban roads and extended the idea 'stroke' road to 'natural road' based on the Gestalt principle of 'good continuity'. They claimed that natural road network captures several essential characters of geographic space and navigation at human perception level.…”
Section: Review On Using Space Syntax To Exploring Traffic Patternsmentioning
confidence: 99%
“…Scientific studies on this issue bring a new view that a group of network nodes have more structural dates in comparison with a single one (Wagner, 2008) (Tischendorf, L., Fahrig, L., 2000). This subject begins from the logic of a space syntax, that urban road network are working as a body neural network where movement are employed make simple linear elements in the network that could be able to present line movement in the network system to find natural units (Jiang, B., Zhao, S., Yin, J., 2008). Space syntax emerged from the architectural view to an environment one as logic a analyze space.…”
Section: Introductionmentioning
confidence: 99%